Forging of Foreign Values - Rusu, Ioana (Acta Universitatis Danubius. Juridica, 2022)
In this paper I analyzed the official mentioned with a marginal title, offence that has been recently introduced in Romanian law. The analysis may be useful to students of law schools in the country, as well as to practitioners in the field of criminal law. The novelty element is the analysis of this offence, representing an absolute novelty in Romanian criminal law. The paper is part of a university course to be published in the future in the country.